How many Siphonaria species (Gastropoda: Euthyneura) live in southern South America? - Güller, Marina; Zelaya, Diego Gabriel; Ituarte, Cristian Federico (Journal of Molluscan Studies)
This contribution provides the first integrative revision of the Siphonaria species described and reported from southern South America, by combining information on shell morphology, distal portion of the genital system, radula, molecular data and living animal. More than 200 lots, from all along the Uruguayan, Argentinean and southern Chilean coasts, including the Malvinas (Falkland) Islands and South Georgia, were studied. Among the nine nominal species listed for this area, only the presence of Siphonaria lessonii Blainville, 1827 and S. lateralis Gould, 1846 could be confirmed. The intraspecific variability of these two species along their distributional ranges is examined. Siphonaria magellanica Philippi, 1855 and S. antarctica Gould, 1852 are regarded as probable synonyms of S. lessonii. The Magellanic records of S. tristensis are reassigned to S. lessonii and those of S. macgillivrayi to S. fuegiensis n. sp. The similarity of S. redimiculum Reeve, 1856, S. laeviuscula Sowerby, 1835 and S. lineolata Sowerby, 1835 to the three species confirmed in the studied area is discussed. The Chilean S. laevis Philippi, 1846 is considered a nomen dubium. All available types are figured and a lectotype is designated for S. redimiculum. Fil: Güller, Marina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina Fil: Ituarte, Cristian Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina